Bangladesh : Political Economy of Right to Information - Ahsan, Syed Khaled (World Bank, Washington, DC, 2020)
The Right to Information (RTI) Act, 2009, was a milestone in the legal history of Bangladesh to ensure people’s right to obtain information from the government offices and other organizations. This act covers most bodies owned, controlled, or substantially financed either directly or indirectly by the government and non-governmental organizations (NGOs). The act aims at giving citizens the right to hold the government accountable. In the 1990s, civil society advocated for the RTI Act as one of the best-fitted tools to establish good governance. The act was drafted by the government and civil society organizations (CSOs) together, following an analysis of a few other RTI Acts. A caretaker administration further cemented the path for the introduction of the RTI Act. The Council of Advisors of the caretaker administration approved the RTI Ordinance in September 2008, and it became formally recognized as a law from October 20, 2008. The democratically elected new government passed the RTI Act in March 2009, in the very first session of Parliament. The context of introducing a law for RTI in Bangladesh was different from that of India. The demand came from the grassroots level in India with a 40-day sit-in protest by a citizens’ rights body in 1996. In the case of Bangladesh, it came from Dhaka-based elites and lacked connection with the grassroots (Article 19 2015). The RTI Act, 2009, helps investigative journalism, but that is not the entire goal of this act. The goal is to empower citizens with information and make livelihoods easier for the ones who will otherwise have no means of getting answers from the state or other social actors.